2019
DOI: 10.3390/met9060715
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static and Plate Impact Loading of Cast Magnesium Alloy ML5 Reinforced with Aluminum Nitride Nanoparticles

Abstract: The influence of a small addition of 0.5 wt.% aluminum nitride nanoparticles with an average size of 80 nm on the mechanical properties of a cast magnesium alloy under quasi-static tensile (strain rate 10−4 s−1) and plate impact loading (strain rate 105 s−1) was investigated. The composites were obtained by casting with a special mixing vortex device. After casting, some samples were subjected to heat treatment. The introduction of a small number of particles into the liquid metal led to a decrease in matrix g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…It was found that the introduction of aluminum nitride nanoparticles leads to an increase in the strength and plasticity of the magnesium alloy from 176 to 214 MPa and from 6 to 10%, respectively. The obtained results are in good agreement with previous studies [22]. A significant contribution to the increase in mechanical properties could be made by the refinement of the grain of the alloy [23] according to the Hall-Petch law, however, this mechanism provides for a direct effect of the grain size on the yield stress [24], which does not increase.…”
Section: Az91-aln Alloysupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that the introduction of aluminum nitride nanoparticles leads to an increase in the strength and plasticity of the magnesium alloy from 176 to 214 MPa and from 6 to 10%, respectively. The obtained results are in good agreement with previous studies [22]. A significant contribution to the increase in mechanical properties could be made by the refinement of the grain of the alloy [23] according to the Hall-Petch law, however, this mechanism provides for a direct effect of the grain size on the yield stress [24], which does not increase.…”
Section: Az91-aln Alloysupporting
confidence: 89%
“…A significant contribution to the increase in mechanical properties could be made by the refinement of the grain of the alloy [23] according to the Hall-Petch law, however, this mechanism provides for a direct effect of the grain size on the yield stress [24], which does not increase. It is assumed that the introduction of particles into the grain body can lead to a deviation of a potential crack from the grain boundary into its volume, as well as to a greater involvement of the metal matrix in the process of deformation and fracture [21,22].…”
Section: Az91-aln Alloymentioning
confidence: 99%
“…The hot working properties of an ML5 magnesium alloy that corresponded to AZ91 and was reinforced with 0.5 wt.% AlN nanoparticles were investigated in [13]. The mechanical properties of the nanocomposite were superior to those of the pure alloy in the quasi-static and shock wave tests.…”
Section: Contributionsmentioning
confidence: 99%
“…In this respect, the Mg-metal matrixes of the AZ and AM series are the most used in the automotive industry [24]. Reported reinforcement particles introduced in the Mg-MMCs are carbides (SiC, B 4 C, and ZrC) [25][26][27], oxides (Al 2 O 3 , Y 2 O 3 , and TiO 2 ) [28][29][30], borides (TiB 2 ) [31], nitrides (Si 3 N, AlN, ZrN, and TiN) [27,[32][33][34][35][36][37][38][39][40][41][42], carbon nanotubes [43], and metals (Cu, Ti, Mo, and Bi) [44][45][46][47]. For the manufacture of MMCs, different fabrication techniques have been used [48,49].…”
Section: Introductionmentioning
confidence: 99%